Digital transformation through information technology: the dynamics of the role of teachers in implementing online-based learning - Tafonao, Talizaro; Ditakristi, Agiana Her Visnhu (SAINTIS Publishing, 2022)
The application of technology-based education really requires innovation from teachers. The aim of writing this article is to describe the efforts of teachers in dealing with the dynamics in the digital-based learning process. This article describes the various challenges faced by teachers in maximizing learning in accordance with the demands of the government in mastering technology in learning. But in reality, there are still teachers who have not mastered online platforms. The method used in this study is descriptive qualitative. The results obtained in this study are that teachers are required to have technological knowledge, have the ability (skills) to apply technology, transform with the digital world, and have high creativity in utilizing various existing tools. All the dynamics experienced by teachers so far can be resolved by attending various trainings and workshops to support the ability to teach.